Investigação de genes de resistência às quinolonas e aminoglicosídeos em Klebsiella pneumoniae produtoras de carbapenemases do tipo KPC em hospitais do estado de São Paulo - Tolentino, Fernanda Modesto [UNESP] (2015)
The increase in infection rates by KPC producing K. pneumoniae is a serious global public health problem. These enzymes hydrolyze carbapenems, oxyimino-cephalosporins, cephamycins, and -lactamase inhibitors such as clavulanic acid, sulbactam and tazobactam. In addition, the plasmids carrying blaKPC genes generally harbor other antimicrobial resistance genes. Thus, the aim of this study was to investigate, in a comparative way, the presence of genes conferring resistance to aminoglycosides, quinolones and -lactams between KPC producing K. pneumonia from various hospitals in São Paulo City and from a tertiary hospital located in Sao Jose do Rio Preto, northwest of São Paulo state. The genetic similarity and the clonal relationship among strains were also determined. One hundred isolates were studied: fifty from different hospitals in São Paulo (named SP), and fifty from the Hospital de Base de São José do Rio Preto (named KP). The blaCTX-M gene was detected in 76% of the KP strains and in 58% of the SP strains. Among the KP strains, 68.4% had blaCTX-M-15, 23.7% blaCTX-M-2, 2.6% blaCTX-M-59, 2.6% blaCTX-M-15 and blaCTX M-59 simultaneously, and 2.6% were unidentified. Among the SP strains, 51.7% presented blaCTX-M-2, 37.9% blaCTX-M-15, 2.5% blaCTX-M-15 and blaCTX-M-2 simultaneously, and 5% blaCTX-M-14. Regarding the genes for AMEs, among the seven types investigated, five were detected: aph (3') -VI, aph (3 ') - Ia, aac (6') - Ib, aac (3) -Ia and aac (3) IIa were detected among 95% of the strains, and no difference was observed between KP and SP strains. Among the seven genes for 16S rRNA methyltransferases, only the rmtB was detected, in two SP strains. Concerning genes that determine resistance to quinolones, 42% of he KP and 14% of the SP strains showed qnrB. The oqxAB gene was detected in 56% and 2% of the SP and KP strains, respectively. Molecular typing by ERIC-PCR revealed that genetical...